Contributions of the Re-Orientation as a Strategy for University Retention - De Ortúzar, Victoria (2016)
This paper is in line with the research "Assessment of inclusion strategies in order to reduce university dropouts and re-orientation in other educational and training places" (Gavilán, M. 2014-2017). That research, still in progress, is intended to assess inclusion strategies aiming at reducing university dropouts that are carried out in the significant courses of the different fields of knowledge at the National University La Plata. This study seeks to account for the problematic issue concerning the dropout of and admission to the academic system and the strategies and considerations its approach has generated. Special emphasis is placed on the analysis of the program "back to see/look again" working on the concept of reorientation as a possible strategy in relation to university retention.